1997
DOI: 10.1182/blood.v89.3.767
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Specific Immunoassay for Plasma Two-Chain Factor VIIa: Investigation of FVIIa Levels in Normal Individuals and in Patients With Acute Coronary Syndromes

Abstract: We report the development of an enzyme-linked immunosorbent assay (ELISA) that is specific for factor VIIa (FVIIa). This assay uses a neoantigen specific capture antibody directed to the amino acid peptide sequence N terminal to the FVII cleavage activation site. The antibody exhibits ∼3,000-fold greater reactivity to FVIIa than FVII on a molar basis. Experiments using plasma with added (exogenous) human FVIIa gave quantitative recovery in the ELISA over a range of 0.20 to 3.2 ng/mL of FVIIa. The intra- and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 20 publications
3
26
0
Order By: Relevance
“…The levels of FVII:C and FVII:Ag, as well as free TFPI, were within normal ranges as compared with the control group. This finding is in accordance with the results published by other groups (Morrissey et al, 1993;Philippou et al, 1997;Giannitsis et al, 2000). The present study showed for the first time that the treatment of unstable angina using a LMWH (enoxaparin) inhibits in vivo the generation and the activity of factor VIIa.…”
Section: Discussionsupporting
confidence: 94%
“…The levels of FVII:C and FVII:Ag, as well as free TFPI, were within normal ranges as compared with the control group. This finding is in accordance with the results published by other groups (Morrissey et al, 1993;Philippou et al, 1997;Giannitsis et al, 2000). The present study showed for the first time that the treatment of unstable angina using a LMWH (enoxaparin) inhibits in vivo the generation and the activity of factor VIIa.…”
Section: Discussionsupporting
confidence: 94%
“…However, caution should be used in these interpretations. First, the validity of the FVIIa used in this study has been questioned recently and it may be that the levels we obtained are overestimations due to a possible in vitro activation of factor VII (Philippou et al, 1997). Alternatively, it is possible that the antibody used by Philippou et al (1997) cannot recognize the FVIIa bound to lipid or tissue factor.…”
Section: Discussionmentioning
confidence: 93%
“…First, the validity of the FVIIa used in this study has been questioned recently and it may be that the levels we obtained are overestimations due to a possible in vitro activation of factor VII (Philippou et al, 1997). Alternatively, it is possible that the antibody used by Philippou et al (1997) cannot recognize the FVIIa bound to lipid or tissue factor. In addition, the FVIIa clotting assay which uses a soluble mutant of tissue factor may measure partially activated FVII forms which are not recognized by immunoassay.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Philippou et al generated a polyclonal antibody directed against the C-terminal part of the FVIIa light chain, which displayed >3000-fold greater reactivity to FVIIa than FVII. 19 Andersen et al 18 reported on antibodies that show preferential binding to FVIIa and stimulated FVIIa activity. Most recently, a llama-derived single-domain antibody (sdAb) that binds to FVIIa but not to FVII has been described.…”
Section: Introductionmentioning
confidence: 99%